2009
DOI: 10.1590/s0100-736x2009000800003
|View full text |Cite
|
Sign up to set email alerts
|

Análise histomorfométrica da matriz extracelular do linfonodo poplíteo de cães naturalmente infectados por Leishmania (L.) chagasi

Abstract: Nas Américas, a leishmaniose visceral canina é causada por Leishmania (Leishmania) chagasi, um protozoário intracelular obrigatório do sistema fagocítico mononuclear; as principais alterações histológicas associadas a essa doença ocorrem nos em órgãos linfóides. Apesar de o cão ser considerado o principal mantenedor e disseminador da leishmaniose no ambiente urbano, são escassos estudos dos aspectos histopatológicos e histomorfométricos, em cães naturalmente infectados com L. chagasi, que investiguem a interaç… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
(18 reference statements)
0
1
0
Order By: Relevance
“…These changes may be related to deleterious effects in the inflammatory infiltrate (Giunchetti et al 2006) or to mechanisms for evasion of the host's immune response that the parasite induces (Lira et al 1997). On the other hand, Kondo et al (2009) found that type I collagen was gradually replaced by type III collagen in the popliteal lymph nodes of dogs with VL.…”
Section: Discussionmentioning
confidence: 99%
“…These changes may be related to deleterious effects in the inflammatory infiltrate (Giunchetti et al 2006) or to mechanisms for evasion of the host's immune response that the parasite induces (Lira et al 1997). On the other hand, Kondo et al (2009) found that type I collagen was gradually replaced by type III collagen in the popliteal lymph nodes of dogs with VL.…”
Section: Discussionmentioning
confidence: 99%